The Right of Early Access to Criminal Legal Aid in Indonesia: Clear Rule, Clearer Violations - Abbott, Maxwell (Indonesia Law Review, 2018)
This article will examine the right of early access to criminal legal aid in Indonesia, both in theory and in practice. In theory, the right of early access to criminal legal aid (the Right) is clear and firmly established in Indonesian law and international law which applies to Indonesia: individuals under arrest or in detention are entitled to receive legal aid at all stages of the criminal justice process. Therefore, law enforcement may not deny or delay a suspect’s access to a lawyer during the initial procedural stages of arrest, investigation and detention. This article will argue that the Right meets certain criteria of a clear legal rule, as distinguished from a vaguer legal standard, and we would therefore expect a high degree of compliance with the Right. However, in practice, we find frequent violations of the Right in Indonesia. After reviewing evidence of the violations, the article will conclude by briefly addressing several explanations while maintaining that the Right is a clear legal rule.